$s$-Sequence-Covering Mappings on Metric Spaces (Journal of Mathematical Study, 2022)
In this paper, we introduce and study $s$-sequence-covering mappings and1-$s$-sequence-covering mappings, obtain some characterizations of $s$-sequence-coveringand compact images of metric spaces, and prove that every $s$-sequence-covering andcompact mapping in first-countable spaces is a 1-$s$-sequence-covering mapping.